In Situ Growth of Ultrapure Green‐Emitting FAPbBr3‐PVDF Films via a Synergetic Dual‐Additive Strategy for Wide Color Gamut Backlit Display. Issue 8 (25th March 2022) - Yang, Changbin; Niu, Weifan; Chen, Renjing; Pang, Tao; Lin, Jidong; Zheng, Yongping; Zhang, Ruidan; Wang, Zhibin; Huang, Ping; Huang, Feng; Chen, Daqin
Abstract: Elaborate engineering of emitting wavelength of green down‐converter in the spectral range of ≈ 525–535 nm with narrow full‐width at half‐maximum (fwhm < 25 nm) is an essential prerequisite for faithfully reproducing colors in the quantum dot (QD)‐based backlit display. Herein, different from the previous complex synthesis for green films, FAPbBr3 perovskite QDs films are fabricated by a dual‐additive assisted in situ growth strategy. Both C6 H5 CH2 CH2 NH3 + and 1, 4, 7, 10, 13, 16‐hexaoxacyclooctadecane additives are introduced to synergistically tune green emitting (≈ 525–535 nm) with the narrowest fwhm down to 21 nm and the highest photoluminescence quantum yield (PLQY) up to 99%. Improved nanocomposite film with excellent long‐term stability is used to construct a prototype liquid crystal display (LCD) with a wide color gamut (118% National Television System Committee and 88% Recommendation BT 2020), a high saturation, and a remarkable color rendition. The performance is superior to that of the commercial white‐LED‐based LCD, showing a great potential of the present green film for high‐definition display application in the future. Abstract : A dual‐additive assisted in situ growth of green‐emitting FAPbBr3 ‐polyvinylidene fluoride film with narrowest full‐width at half‐maximum of 21 nm and highest photoluminescence quantum yield of 99% is reported. A demoed display using the FAPbBr3 film backlit unit exhibits a wide color gamut, high saturation, and a remarkable color rendition, being superior to commercial display.